2015
DOI: 10.1038/ki.2014.272
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis indicates underreporting of renal dysfunction following endovascular aneurysm repair

Abstract: Deterioration in renal function has been described after endovascular repair of abdominal aortic aneurysms (EVR). The aetiology is multifactorial and represents an important therapeutic target. A need exists to quantitatively summarise incidence and severity of renal dysfunction after EVR to allow better-informed attempts to preserve renal function and improve life expectancy. A systematic search was performed using Medline and Embase for renal function after EVR applying PRISMA statements. Univariate and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 77 publications
1
34
2
1
Order By: Relevance
“…Postoperative renal dysfunction is a significant complication following EVAR and represents the most common post-operative complication in patients under and over 80 years of age (8.4% vs 14.6%) [13,14]. These figures are higher than currently reported in the literature which may be due to underreporting in the literature and a lack of a standardized definition on the subject [14][15][16]. However, these complications did not translate into a higher 30-day mortality rate in octogenarian patients.…”
Section: Discussioncontrasting
confidence: 52%
“…Postoperative renal dysfunction is a significant complication following EVAR and represents the most common post-operative complication in patients under and over 80 years of age (8.4% vs 14.6%) [13,14]. These figures are higher than currently reported in the literature which may be due to underreporting in the literature and a lack of a standardized definition on the subject [14][15][16]. However, these complications did not translate into a higher 30-day mortality rate in octogenarian patients.…”
Section: Discussioncontrasting
confidence: 52%
“…post-operative year is further supported by a meta-analysis which has shown that 18% of patients have developed "clinically important renal dysfunction" at 1 year (defined as rise in SCr>30% compared to baseline). 66 This meta-analysis has, however, not reported AKI incidence using standardised criteria and employed suboptimal measures of renal decline over the long-term. 67 In our series investigating long-term renal decline (at 5 years) after Table 2 lists all large recent studies that evaluated AKI in TAVR patients.…”
Section: Association Of Aki With Mortality Morbidity and Long-term mentioning
confidence: 99%
“…We recently demonstrated that patients undergoing elective EVAR are at significant risk of developing AKI, with a prevalence of 19% (8). A meta-analysis showed that 18% of patients undergoing EVAR will have a clinically significant increase in their serum creatinine (SCr) after 1 year (9). Previous studies have also demonstrated a greater decrease in eGFR for patients who undergo EVAR for the first year compared with the general population (6,10).…”
Section: Introductionmentioning
confidence: 87%